2009
DOI: 10.1111/j.1365-2702.2008.02728.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on professional values among nurses in Taiwan

Abstract: Nurses' awareness of their own values and of how these values influence their behaviour is an essential component of humanistic nursing care. Nursing educators need to develop better strategies for reflection and integration of both personal and professional philosophies and values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 17 publications
4
42
0
2
Order By: Relevance
“…The findings reveled that most of the study sample were in the age group between 31-36 years old, female, single, with the years of experience of more than and equal to 5 years in nursing care. This findings supported by the study which was done by Shih et al 8 in 2008 under the title Perspectives on professional values among nurses in Taiwan which they found the same results. 8 Concerning the nurse's values about nursing which contained 9 value domains of Human dignity, Social justice, Autonomy in decision making, Precision and accuracy in caring, Responsibility, Human relationship, Individual and professional competency, Sympathy, and Trust making, most of the nurses have very good information regarding these values in high rate.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The findings reveled that most of the study sample were in the age group between 31-36 years old, female, single, with the years of experience of more than and equal to 5 years in nursing care. This findings supported by the study which was done by Shih et al 8 in 2008 under the title Perspectives on professional values among nurses in Taiwan which they found the same results. 8 Concerning the nurse's values about nursing which contained 9 value domains of Human dignity, Social justice, Autonomy in decision making, Precision and accuracy in caring, Responsibility, Human relationship, Individual and professional competency, Sympathy, and Trust making, most of the nurses have very good information regarding these values in high rate.…”
Section: Discussionsupporting
confidence: 81%
“…This findings supported by the study which was done by Shih et al 8 in 2008 under the title Perspectives on professional values among nurses in Taiwan which they found the same results. 8 Concerning the nurse's values about nursing which contained 9 value domains of Human dignity, Social justice, Autonomy in decision making, Precision and accuracy in caring, Responsibility, Human relationship, Individual and professional competency, Sympathy, and Trust making, most of the nurses have very good information regarding these values in high rate. All of the findings in the present study were agreed by many studies which were done in different countries in a different time.…”
Section: Discussionsupporting
confidence: 81%
“…Nurses' ranking human dignity first was consistent with an item in the first sub-dimension of NPVS, which was, ''A nurse provides healthcare without any regard to the individuals' social and economic statuses, personal characteristics and health problems, with respect to human dignity and individuality.'' Similarly, the studies by Kantek et al, 23 Kaya et al, 10 Shih et al, 15 and Ersoy 24 found that the most important professional value was human dignity. Subcomponents of professional values can vary among cultures.…”
Section: Discussionmentioning
confidence: 80%
“…Nursing professional values encompass dignity and respect, safeguarding of privacy, responsibility, patient safety, accountability, competence, collaboration, professional behaviour, commitment to the patient, responsibility for practice, duty to themselves and a role in advancing the profession in a changing society (Witt & de Almeida , Shih et al . , Badcott , Gallegos & Sortedahl ).…”
Section: Introductionmentioning
confidence: 95%